Deep-learning based detection of vessel occlusions on CT-angiography in patients with suspected acute ischemic stroke - Gianluca Brugnara; Michael Baumgartner; Edwin David Scholze; Katerina Deike-Hofmann; Klaus Kades; Jonas Scherer; Stefan Denner; Hagen Meredig; Aditya Rastogi; Mustafa Ahmed Mahmutoglu; Christian Ulfert; Ulf Neuberger; et al. (Nature Communications)
Abstract Swift diagnosis and treatment play a decisive role in the clinical outcome of patients with acute ischemic stroke (AIS), and computer-aided diagnosis (CAD) systems can accelerate the underlying diagnostic processes. Here, we developed an artificial neural network (ANN) which allows automated detection of abnormal vessel findings without any a-priori restrictions and in <2 minutes. Pseudo-prospective external validation was performed in consecutive patients with suspected AIS from 4 different hospitals during a 6-month timeframe and demonstrated high sensitivity (≥87%) and negative predictive value (≥93%). Benchmarking against two CE- and FDA-approved software solutions showed significantly higher performance for our ANN with improvements of 25–45% for sensitivity and 4–11% for NPV (p ≤ 0.003 each). We provide an imaging platform ( https://stroke.ccibonn.ai/ ) for online processing of medical imaging data with the developed ANN, including provisions for data crowdsourcing, which will allow continuous refinements and serve as a blueprint to build robust and generalizable AI algorithms.